2012
DOI: 10.1111/1556-4029.12005
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the NMI01 Marker for a Population Database of Cannabis Seeds

Abstract: We have analyzed the distribution of genotypes at a single hexanucleotide short tandem repeat (STR) locus in a Cannabis sativa seed database along with seed-packaging information. This STR locus is defined by the polymerase chain reaction amplification primers CS1F and CS1R and is referred to as NMI01 (for National Marijuana Initiative) in our study. The population database consists of seed seizures of two categories: seed samples from labeled and unlabeled packages regarding seed bank source. Of a population … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 3 publications
2
9
0
Order By: Relevance
“…Many studies have been performed with different types of molecular markers to evaluate the diversity among accessions in C. sativa, revealing that the crop is genetically very diverse (e.g., Shirley et al, 2013;Gao et al, 2014;Sawler et al, 2015). Amazingly, there are very few studies evaluating the intra-varietal diversity of C. sativa, which is very important for selection, breeding and developing uniform cultivars.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have been performed with different types of molecular markers to evaluate the diversity among accessions in C. sativa, revealing that the crop is genetically very diverse (e.g., Shirley et al, 2013;Gao et al, 2014;Sawler et al, 2015). Amazingly, there are very few studies evaluating the intra-varietal diversity of C. sativa, which is very important for selection, breeding and developing uniform cultivars.…”
Section: Introductionmentioning
confidence: 99%
“…indica cultivars had four or more (up to eight) individuals, which is a limited number of cultivars to draw general conclusions. Shirley et al (2013) using a single SSR marker found several genetic profiles in DNA extracted from individual seeds of each of several C. sativa var. indica accessions, with an important level of heterozygous loci.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of DNA from embryos extracted via the developed protocol enabled successful SSR characterization from 2n zygotes. Herein, we found that C. sativa presents a certain degree of heterozygosis; thus, DNA extraction from whole seeds (achenes) could theoretically result in the amplification of three alleles when the maternal plant is heterozygous and the allele carried by the male gamete is different from the maternal alleles . However, we did not find any SSR profiles with three alleles, indicating a lack of contamination in the embryo tissues resulting from the presence of tissue from the seed testa or achene pericarp.…”
Section: Discussionmentioning
confidence: 70%
“…The 11 genomic SSR primers used in this study have previously been used to detect many alleles and represent an addition to the available SSR markers for the genetic characterization of Cannabis . The fact that genomic SSR markers are usually highly polymorphic compared with EST‐SSRs is likely a primary factor in this high degree of polymorphism and suggests that the development of further SSRs for identification purposes could benefit from the availability of the genome sequence .…”
Section: Discussionmentioning
confidence: 99%